Emerging technologies and digital transformation in the manufacturing industry - Tiburcio, Agustin; Hernandez-Gonzalez, Luis Manuel; Tiwari, Sanju 1979-; Ortiz-Rodriguez, Fernando 1974- (IGI Global, 2023)
Emerging Technologies and Digital Transformation in the Manufacturing Industry offers a comprehensive solution to the pressing challenges faced by the manufacturing industry. As manufacturers grapple with the need to adapt to changing customer expectations and embrace emerging technologies, this book provides a timely and relevant resource. Edited by esteemed scholars, it features high-quality chapters that delve into technology-driven approaches, such as Internet-connected machinery, artificial intelligence, and sensors, with the aim of enhancing efficiency, productivity, and overall performance in manufacturing processes.Covering key topics such as machine learning, blockchain technologies, big data, and the industrial Internet of Things (IIoT), the book explores transformative concepts like digital twins, extended reality, and the impact of 5G and edge computing. With contributions from authoritative experts, this book serves as an indispensable tool for students, researchers, and IT professionals in manufacturing plants. By offering practical guidance and insights, Emerging Technologies and Digital Transformation in the Manufacturing Industry equips readers with the knowledge and tools needed to navigate the complexities of digital transformation and seize the opportunities presented by emerging technologies. It is academic rigor and practical applicability makes it a valuable resource that is poised to have a significant impact on the manufacturing IT community and academic scholars worldwide, enabling a successful journey toward a more efficient and resilient future in the manufacturing industry.